Decápodes holo e meroplanctônicos do Atlântico Sul subtropical - Almeida, André Marafon de (2015)
The presente study describes the spatial variation of the Holoplanktonic and Meroplanktonic Decapods in a region of the subtropical South Atlantic Ocean, that covers important oceanographic features such as the Brazil Current (BC) and the Malvinas Current (MC), the Subtropical Convergence, the South Atlantic Central Water (SACW) recirculation, South Atlantic Current (SAC), South Equatorial Current (SEC), Benguela Current system and Agulhas Current (AC). Covering an area with important geological features such as the Mid-Oceanic Ridge, the Vitoria-Trindade seamount chain, the Rio Grande Rise and the Walvis Ridge. This study was carried out with Holoplanktonic and Meroplanktonic Decapods collected in three cruises totaling 114 samples. The first two cruises covered 31 stations at the Vitória-Trindade submarine mountain chain and adjacent region in November and December 2011. The third cruise collected 83 samples between October and December 2009, with both latitudinal profiles (20° 16 e 30°S) involving Brasil – Africa in South Atlantic Subtropical Gyre. The first two cruises had 30 families of Decapods (holoplanktonic and meroplanktonic) identified , divided into 85 taxa from which 47 occurred exclusively on the VitóriaTrindade chain, 28 were broadly distributed in the study area and the other 10 were found only in the adjacent open ocean stations. The ecological index registered along the Vitória-Trindade chain indicates that this environment is highly rich and diverse, composed by holoplanktonic and meroplanktonic Decapods, being this the main environment in terms of richness and diversity for planktonic Decapods in the South Atlantic. The third cruise that collected holoplanktonic and meroplanktonic Decapods evaluated three longitudinal sectors: West sector (SW), Central sector (SC) and East sector (SE), between two longitudinal profiles 20° and 30°S. Holoplanktonic and meroplanktonic Decapods occurred in 31 of the 83 stations, with 22 taxa identified belonging to 10 families: Penaeidae, Luciferidae, Sergestidae, Oplophoridae, Disciadidae, Palaemonidae, Callianassidae, Axiidae, Portunidae e Galatheidae. In general, there is no latitudinal variation in abundance, diversity and equitability of holoplanktonic and meroplanktonic Decapods. Cluster, similarity and variance analysis allows us to conclude that holoplanktonic and meroplanktonic Decapods are heterogeneously distributed along the analyzed sectors. The results indicate that the epipelagic layer of the subtropical South Atlantic region at the 20 and 30° latitudes show low richness, diversity and abundance of holoplanktonic and meroplanktonic Decapods, which are positively correlated with higher temperatures and salinity noticeably in the West Sector (SW) of the study area, where these abiotic factors limit spatial distribution of these crustaceans in the subtropical South Atlantic.